Boredom: a comprehensive study of the state of affairs - Ros Velasco, Josefa (THÉMATA. Revista de Filosofía, 2017)
A literature shortage is one of the major complaints made by boredom researchers in all fields of study. This claim passes from one study to another without being questioned, thus hampering the understanding of the true state of the issue. In response, this paper demonstrates that it is, in fact, not the case that there is a shortage of literature on boredom; rather, there exists a lack of thematic variety and issues of linguistic accessibility. The paper also falsifies the claim that, up until the beginning of the 2000, there were only a few studies on boredom published each year. The results are based on a comprehensive database which includes the total population of studies on boredom and classifies them according to linguistic, thematic and chronological criteria.